Management of bipolar depression with Lamotrigine: an antiepileptic mood stabilizer - Kedar S Prabhavalkar; Nimmy Baby ePoovanpallil; Lokesh Kumar Bhatt (Frontiers Media S.A., 2015)
The efficacy of lamotrigine in the treatment of focal epilepsies have already been reported in several case reports and open studies, which is thought to act by inhibiting glutamate release through voltage-sensitive sodium channels blockade and neuronal membrane stabilization. However, recent findings have also illustrated the importance of lamotrigine in alleviating the depressive symptoms of bipolar disorder, without causing mood destabilization or precipitating mania. Currently, no mood stabilizers are available having equal efficacy in the treatment of both mania and depression, two of which forms the extreme sides of the bipolar disorder. Lamotrigine, a well established anticonvulsant has received regulatory approval for the treatment and prevention of bipolar depression in more than 30 countries worldwide. Lamotrigine, acts through several molecular targets and overcomes the major limitation of other conventional antidepressants by stabilizing mood from 'below baseline' thereby preventing switches to mania or episode acceleration, thus being effective for bipolar I disorder. Recent studies have also suggested that these observations could also be extended to patients with bipolar II disorder. Thus, lamotrigine may supposedly fulfill the unmet requirement for an effective depression mood stabilizer.